Predictors of No-Reflow in Patients undergoing Primary Percutaneous Coronary Intervention for Acute ST Elevation Myocardial Infarction at Tabba Heart Institute Karachi - Awais Ahmad Nizami, Shehzad Ahmad, Bashir Hanif, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the predictors of no-reflow in patients undergoing Primary Percutaneous Coronary Intervention (PPCI) for acute ST elevation myocardial infarction (STEMI) at Tabba Heart Institute Karachi. Study duration: The study was carried out from September 2020 to September 2021. Methods: An observational study that was conducted at Tabba heart Institute Karachi. All patients with acute ST elevation myocardial infarction (STEMI) presenting within 12 hours of symptoms who undergoing primary PCI were included in the study. The patients were categorized Angiographically as no –reflow (with Thrombolysis in Myocardial Infarction (TIMI) <3 and reflow (TIMI-3) flow groups. The data regarding age and gender, type of MI, time from symptoms onset, co-morbid conditions like diabetes mellitus, hypertension, smoking, baseline Thrombolysis In Myocardial Infarction Trials (TIMI flow), infarct related artery (IRA), diameter of stent used, and the TIMI flow in IRA after the completion of procedure but before the use of intracoronary adenosine if needed, was recorded on a pre-designed proforma. The data was analyzed using SPSS 20.0. Results: Total 296 patients who underwent primary PCI after acute MI were enrolled in the study. Mean age of the study population was 57±11 years. No reflow was present in 31.4% of patients. No reflow was more common in patients with age more than 60 years, females, symptom onset to primary PCI time of more than 6 hours, LAD infarct, and baseline TIMI flow < 2. Conclusion: During primary PCI, no reflow occurs in a significant percentage of patients and is predictable by a number of factors which should be kept in mind to minimize the incidence of no reflow. Key words: No reflow, acute myocardial infarction, primary PCI